Analysis Of Non-Verbal Communication On Application X In @arabmemesss: Roland Barthes’ Semiotics Perspective - Pratiwi, Fanisa Ira Ronia; Yurisa, Penny Respati (Universitas Cokroaminoto Palopo, 2025)
This research focuses on Roland Barthes semiotics which aims to analyze the denotation and connotation meanings of memes in the social media account @arabmemesss on the X app. As a form of non-verbal communication, memes not only entertain but also convey cultural and social messages. This research uses a descriptive qualitative method, with data collection methods in the form of reading and recording. Data analysis was conducted using data analysis techniques from Miles and Huberman, namely data reduction, data presentation, and conclusion drawing. The results showed that each meme contains various layers of meaning, including; humor, satire, and self-reflection. The memes not only represent the expression of human emotions, but also reveal Arab culture wrapped in humor. The @arabmemesss account on the X app shows that memes reflect hidden emotions and can only be understood through in-depth analysis. In addition, the humor and satire often used in memes play an important role in conveying a deeper message. This research deepens the understanding of the application of Roland Barthes' semiotic theory in the analysis of non-verbal communication through memes.